PENGARUH KONFLIK PERAN GANDA DAN PSYCHOLOGICAL WELL- BEING TERHADAP KINERJA (Studi Pada Perawat Wanita RSUD S.K.Lerik Kota Kupang) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
The purpose of this study is to describe the effect of double role conflict and psychological well-being on the performance of female nurses in S.K.Lerik Public Hospitals Kupang City. Research methodology: The study was conducted with a qualitative approach. Data collection was carried out by filling out the questionnaire by 38 female nurses who were sampled. Data processing is performed by multiple linear regression analysis. Results: The results of this study indicate the influence of dual role conflict variables and psychological well-being on the performance of female nurses in the S.K.Lerik Public Hospital Kupang City both partially and simultaneously. Limitations: This study only discusses the influence of multiple role conflict variables and psychological well-being on the performance of female nurses at the S.K.Lerik Regional Hospital in Kupang. Contribution: This research can be used as scientific information in the field of human resource management..